State space representation for synthetic time series models and BoxJackeys models with an application in the Iraqi Stock Exchange - افتخار عبد الحميد النقاش; هدى عدنان توفيق (Iraqi Journal for Administrative Sciences, 2025)
The State space models is one of the ways of time series analysis which deals with the phenomena manner and its explanation through different times, these models have been used in the field of Engineering after Kalman (1960) has published his research , its using has been expanded in the other sciences such as Economics ,Medicine ,Physical Sciences ,Quality Controlling and others. The research aims to use The State space models in the forecasting by series of numbering the daily traded shares for the Banks Sector in Iraq Stocks Exchange, it has been model every component (Trend, Seasonal and Cyclical) these components have been put in The State space model . It has been built Box-Jenkins model ARMA (1, 1) for the studies series by State space model . The Research has resulted to the Identified Model ARMA (1, 1) which has been formed by State space model is a suitable model to describe the series data during noticing results and giving it forecasting values nearer to the real while Local Level Model gave stable forecasting values and equal to (6.0112e+008), so the Researcher has recommended to depend the ARMA (1, 1).